KAJIAN KARAKTERISTIK DAN PENGARUH NISBAH PEREAKSI, pH AWAL REAKSI DAN SUHU REAKSI TERHADAP BERAT RENDEMEN NATRIUM LIGNOSULFONAT - Michael Lim, Eric Wirtanto, Zuhrina Masyithah (Jurnal Teknik Kimia USU, 2012)
Indonesia as one of the biggest producer of crude palm oil in the world for sure will have some problems on handling their wastes such as palm shell. Palm shell is one of industrial wastes that having low commercial value with contain about 29,4 % lignin component which very potential for  use as new raw material for Sodium LignoSulfonat production. Sodium lignosulphonate (SLS) is a product of isolated lignin sulphonation process using NaHSO3 as sulphonation agent.The research begins with isolated lignin from palm shell amd continued with sulphonation with mass ratio of palm shell lignin – NaHSO3(b/b) of 1:0.2, 1:0.3, and 1:0.5 and initial pH of 6,7 and  8  at temperature 85 oC and 95 oC. Studies on the efeect of various ratio of palm shell lignin – NaHSO3 and initial pH and temperature for the sulphonation raction showed an increasing yield  of (SLS) yield. The highest SLS yield of 51,2 % was obtained under condition mass ratio of palm shell lignin – NaHSO3 1:0.3, pH 7 and at temperature 95 oC. The resulted SLS was dark brown, purity 66,1782, pH level between 6-7, water soluble.Key words : palm shell lignin, lignin, surfactant, sodium lignosulphonate